Modeling the relationship between academic passion and disciplinary behavior towards the academic success of physical education: mediated by learning attention - Mudian, Deni; Prasetiyo, Arif Fajar; Raman, Arumugam; Setiawan, Edi (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: Academic success is the ultimate goal that students must achieve, but the factors that influence it are still unclear. Objectives: This study aims to explore the mediating role of attention to learning in the relationship between academic passion and disciplinary behavior on the academic success of physical education students at the high school level. Methods: The quantitative research method with a cross-sectional design was carried out on 456 high school students in Subang city. Data collection used a structured questionnaire that included a Passion Scale to measure academic passion, a Self-Discipline Scale to assess disciplinary behavior, an Attention in Learning Scale to measure attention to learning, and a multidimensional instrument to evaluate academic success. Results: The findings of the study showed that academic passion had a significant effect on attention to learning (β = 0.42; p < 0.001). Disciplined behavior also showed a significant influence on attention to learning (β = 0.38; p < 0.001). Academic passion showed that significantly influence academic success (β = 0.23; p < 0.001). Disciplined behavior also showed a significant influence on academic success (β = 0.19; p < 0.001). Learning attention showed a significant influence on academic success (β = 0.51; p < 0.001). In addition, we observed a significant effect of academic passion on disciplined behavior. (β = 0.58; p < 0.001). Conclusion: This study confirms that academic passion and disciplinary behavior contribute to the academic success of physical education students through direct and indirect mechanisms via the mediation of attention to learning.